Arteterapia e envelhecimento ativo e saudável: processos terapêuticos para a busca da felicidade no momento presente - Donato, Aline Corazza de (2024)
The main focus of this study is to reflect on the processes of Art Therapy as a primary resource in the search for human integrity during the aging process, discussing issues that permeate the relationship between happiness, positive emotions, and integral well-being with quality of life. The methodology used was to carry out in-person Art Therapy experiences with a group of women in middle and late adulthood in a therapeutic space in the north of Rio Grande do Sul, in which subjective themes related to happiness were applied, such as true love, gratitude, and forgiveness, combined with the tangible experience of the senses for happiness, using various artistic techniques. The results will be presented in writings, through reports of the activities developed, prioritizing a welcoming narrative, focusing on dialogue and reflection, with the aim of providing an opportunity for the exchange of experiences. The narratives reveal the universe of the participants, translated in the form of internal conflicts and emotions, the stimulation of creativity, the strengthening of social bonds and the development of new skills. The reflections made possible the analysis of qualitative data collected through the participants' experiences, which revealed an increase in self-esteem, flexibility and autonomy, contributing to the development of a more positive perception of life, the ability to deal with adversity, a feeling of happiness, strengthening of internal resources and overall well-being. In the end, the study indicates that Art Therapy can be an effective tool for promoting active, healthy and happy aging.